PERSPECTIVE OF FEDERAL PUBLIC POLICY REPRESENTATIVES ON FOOD LABELS - Mônica Cecília Santana Pereira; Maria Cristina Pinto de Jesus; Helena Siqueira Vassimon; Maria de Fátima Lobato Tavares (Universidade do Estado do Rio de Janeiro, 2017)
Purpose: Knowing the perspective of federal public policy representatives on food labels in Brazil. Methodology: It is a descriptive, exploratory, qualitative approach, in which representatives of institutions responsible for the elaboration and review of regulations on general and nutritional food labeling in Brazil were interviewed in 2016. Data treatment was done through the content analysis technique. Results: Respondents considered food label as a right to information and highlighted advances such as the mandatory nutrition labeling. They cited obstacles that delay the regulatory process, such as the standardization process of the legislation with Mercosur countries, excessively technical information and conflicts of interest, including the lobbying of industries. Among the challenges, there was the need to establish a closer relationship between nutrients and ingredients, and the adoption of a frontal nutrition labeling model, in order to make nutrition information available in a clear and concise manner. Conclusions: These results may support professionals who act directly or indirectly with consumers in the elaboration of strategies to help them choose food through nutritional labeling and ingredient lists, in order to promote health and improve the quality of life. DOI: 10.12957/demetra.2017.29571